Out of Sight Till Tonight! - Rabe, Tish; Ruiz, Aristides; Mathieu, Joe, 1949- (New York : Random House, 2015)
"The Cat in the Hat takes Sally and Nick to visit with nocturnal animals and to explore their special adaptations for living in the dark"--
Includes bibliographical references (page 43) and index.
Keywords: Cat in the Hat (Fictitious character) -- Juvenile literature; Nocturnal animals -- Juvenile literature; Adaptation (Biology) -- Juvenile literature; Cat in the Hat (Fictitious character); Nocturnal animals; Adaptation (Biology)